1999
DOI: 10.1046/j.1365-2362.1999.00520.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression pattern of tumour necrosis factor receptors in subcutaneous and omental human adipose tissue: role of obesity and non‐insulin‐dependent diabetes mellitus

Abstract: These results indicate that severe obesity in women is characterized by increased amounts of the two TNF receptor mRNAs. The role of this up-regulation for the development of obesity-associated insulin resistance remains to be elucidated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
69
3
5

Year Published

1999
1999
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(84 citation statements)
references
References 24 publications
7
69
3
5
Order By: Relevance
“…versus s.c. adipose tissue. [34][35][36] In most cases, however, this difference seems to be attributable to increased cytokine or chemokine expression in the stromal-vascular fraction, so that our data are in line with other studies investigating isolated adipocytes and correcting for macrophage gene expression. 37,38 We also studied the effect of donor BMI on IP-10 release of mature adipocytes, but found only a nonsignificant trend towards increased IP-10 secretion in obese donors, whereas a statistically significant positive association between donor BMI and release of macrophage migration inhibitory factor has recently been demonstrated by us using the same methodology.…”
Section: Discussionsupporting
confidence: 90%
“…versus s.c. adipose tissue. [34][35][36] In most cases, however, this difference seems to be attributable to increased cytokine or chemokine expression in the stromal-vascular fraction, so that our data are in line with other studies investigating isolated adipocytes and correcting for macrophage gene expression. 37,38 We also studied the effect of donor BMI on IP-10 release of mature adipocytes, but found only a nonsignificant trend towards increased IP-10 secretion in obese donors, whereas a statistically significant positive association between donor BMI and release of macrophage migration inhibitory factor has recently been demonstrated by us using the same methodology.…”
Section: Discussionsupporting
confidence: 90%
“…The adipose tissue expression of TNF-a mRNA has already been described in rodent models of obesity and also in humans (2,13). Subcutaneous fat depots exhibited 1.67-fold higher TNF-a mRNA expression Figure 4 Correlation between visceral adipocyte cell volume and (a) serum TNF-a, (b) serum sTNFR-2 and (c) fasting C-peptide concentrations in the subjects studied.…”
Section: Discussionmentioning
confidence: 77%
“…-have also been observed (5). Conflicting results concerning the differences in subcutaneous and visceral expression of TNF-a have been published (2,6,7).…”
Section: Introductionmentioning
confidence: 99%
“…Like leptin, TNF-a is known to be overexpressed in human obesity (28)(29)(30). Previous short-term in vivo studies showed a stimulatory effect of TNF-a on leptin gene expression and serum leptin concentrations in rodents after administration of TNF-a (14,15).…”
Section: Discussionmentioning
confidence: 99%